UW-River Falls parking survey - Trechter, David; Parks, Denise (My University, 2005)
This survey was developed for the UW-River Falls Parking Office to solicit their views about parking on and around campus. The survey was sent to faculty and staff, students living in River Falls, and commuter students.
22 p.
Keywords: University of Wisconsin-River Falls; University of Wisconsin-River Falls. Parking Office; University of Wisconsin-River Falls--Parking; Parking; Campus parking; Automobile parking--Wisconsin--River Falls